PENGARUH FEMINISME DEWAN, GRI ADOPTION DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Kasus Pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi yang terdaftar di Bursa Efek Indonesia periode 2013-2017) - Muslih, Muhamad; Klarisa, Nadya (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
CSR disclosure is an important topic that proves whether the company isresponsible for economic, environmental and social factors or not. Company activities havean impact that can harm stakeholders, especially those around the company. Therefore thecompany must disclose its social activities into social responsibility reports to prove thecompany's commitment to the economy, environment and social.This study aims to analyze what factors can affect corporate social responsibilityreports. This study intends to determine whether the independent variables (board feminism,GRI adoption, and firm size) have a simultaneous or partial effect on the dependent variable(Corporate social responsibility disclosure).This study uses a population of infrastructure,utility and transportation sector companies listed on the Indonesia Stock Exchange from 2013to 2017. This research uses purposive sampling technique and obtained 8 companies with a 5-year research period, so that 40 sample data were obtained. The method of data analysis inthis study is panel data regression using software eviews 10.The results of this study state that board feminism is divided between the board ofdirectors' feminism and the boarder's feminism, the GRI adoption and the size of the companyjointly influence the disclosure of corporate CSR in the infrastructure, utilities andtransportation sectors for the period 2013-2017. Firm size has a significant negative effect onCSR disclosure. While board feminism and GRI adoption do not affect CSR disclosure.